Training future describers: A practice report from an audio description classroom - Jankowska, Anna Magdalena (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2020)
Over the past few years, we have been observing an exponential growth in audio description (AD). This has resulted in a growing need for trained AD professionals and, consequently, for AD training. While the ADLAB PRO project helped define the professional profile of the audio describer and produced a range of training materials, there is still considerable room for other AD training approaches to be shared with a view to inspiring AD trainers when creating their courses. Thus, this practice report presents selected exercises that I have been developing since 2009, when I first started teaching AD both at university and outside academia (e.g., during dedicated courses for broadcasters, NGOs and cultural institutions), presenting their learning outcomes and framing them within the ADLAB PRO framework of competencies for professional audio describers. All the activities offered in this article are based on my professional experience as an academic teacher and researcher and also as a professional describer and accessibility manager who overlsees the entire AD production process: from negotiating with clients through production (scripting, proofs, recording, quality control) to product delivery and on-site assistance.